The Conceptof Family Education In Nurcholish Madjid's Perspective - Fathan Arismawan; Nurfuadi Nurfuadi (Edumaspul: Jurnal Pendidikan, 2023)
This study aims to know the literature of the concept of education in a family in the perspective of Nurcholish Madjid. The research method used is Library Reaserch so that books and articles obtained from Google Scholar, Scopus and also articles indexed by WOS are the main ingredients in this study. Furthermore, it is analyzed using a Content Analysis approach. Based on the research conducted, the results were found, if not excessive if the research carried out can be a reference in research, especially those related to education in the family. The position of this paper among the works of researchers who have studied Nurcholish Madjid's thought is clearly different. Because this research will specifically and intensively examine Nurcholish Madjid's thought which is a critical dialogical (ijtihad) in the context of contemporary problems. The freedom and depth of his thinking is an intellectual treasure that can be an inspiration and reflection in answering current problems, especially in the field of education in the family.